Remote Sensing and Geospatial Technologies in Public Health - Fazlay S. Faruque (Ed.) (MDPI - Multidisciplinary Digital Publishing Institute, 2018)
This book demonstrates the utilization of remote sensing and geospatial technologies for a wide range of public health studies. Although remote sensing and geospatial technologies have been successfully applied for more than 50 years, continuous advancements are essential to better understand the complex environment around us that impacts our health and well-being. Thankfully, the availability of spatial analytical tools and necessary data have enabled us to reveal multifaceted, obscured spatial relationships that would have been unexplored otherwise. Now, we are able to make more precise and effective public health-related decisions. However, without a proper understanding of the methodologies, applying these tools may result in inaccurate findings for decision-making. With 15 selected papers, this book covers diverse topics and discusses different methodologies that are fundamentals for spatial analysis in public health. Readers will have an opportunity to experience the advancements in spatial tools, data, and methodologies that are applicable to public health investigations. This book, Remote Sensing and Geospatial Technologies in Public Health, is expected to encourage academicians and professionals to further advance their knowledge in this sub-discipline.